SERINC5 is an unconventional HIV restriction factor that is upregulated during myeloid cell differentiation - Zutz, Ariane; Schölz, Christian; Schneider, Stephanie; Pierini, Virginia; Münchhoff, Maximilian; Sutter, Kathrin; Wittmann, Georg; Dittmer, Ulf; Draenert, Rika; Bogner, Johannes R.; Fackler, Oliver Till; Keppler, Oliver Till (Journal of innate immunity, 2020)
Classical antiviral restriction factors promote cellular immunity by their ability to interfere with virus replication and induction of their expression by proinflammatory cytokines such as interferons. The serine incorporator proteins SERINC3 and SERINC5 potently reduce the infectivity of HIV-1 particles when overexpressed, and RNA interference or knockout approaches in T cells have indicated antiviral activity also of the endogenous proteins. Due to lack of reagents for detection of endogenous SERINC proteins, it is still unclear whether SERINC3/5 are expressed to functionally relevant levels in different primary target cells of HIV infection and how the expression levels of these innate immunity factors are regulated. In the current study, analysis of SERINC3/5 mRNA steady-state levels in primary lymphoid and monocyte-derived cells revealed selective induction of their expression upon differentiation of myeloid cells. Contrary to classical antiviral restriction factors, various antiviral α-interferon subtypes and proinflammatory interleukins had no effect on SERINC levels, which were also not dysregulated in CD4+ T cells and monocytes isolated from patients with chronic HIV-1 infection. Notably, HIV-1 particles produced by terminally differentiated monocyte-derived macrophages with high SERINC5 expression, but not by low-expressing monocytes, showed a Nef-dependent infectivity defect. Overall, these findings suggest endogenous expression of SERINC5 to antivirally active levels in macrophages. Our results classify SERINC5 as an unconventional HIV-1 restriction factor whose expression is specifically induced upon differentiation of cells towards the myeloid lineage.